Effect of Career Development and Job Stress on Turnover Intention Through Job Satisfaction at Character Education Foundation in Depok City - Dewi, Muhtiarti; Iqbal, M (Green Publisher, 2023)
One of the organizations in Depok, which has a competitive advantage in the field of character education, requires quality human resources to realize its goals of creating a generation with character, creativity, and high thinking. The occurrence of employee turnover will be a problem for achieving the goals of the organization. This study aims to analyze the effect of career development and job stress on employee turnover intention using job satisfaction as a mediator. This research uses a quantitative approach and the SmartPLS 3.2.9 application. The population of this study was 174 organization employees with working periods of more than 1 year, and the sample of this study was 122 employees. The result of this study shows that career development has no significant effect on turnover intentions, but has a significant and positive effect on job satisfaction; job stress has a significant and positive effect on turnover intention, and has a significant and negative effect on job satisfaction. Job satisfaction has a significant and negative effect on turnover intentions. Job satisfaction has a mediating role in the influence of career development and job stress on employee turnover intentions. The implication of this research is that reducing employee job stress will increase job satisfaction and reduce employee turnover.